Erratum: Tejeda-Bayron et al. Activation of Glutamate Transporter-1 (GLT-1) Confers Sex-Dependent Neuroprotection in Brain Ischemia. Brain Sci. 2021, 11, 76 - Flavia A. Tejeda-Bayron; David E. Rivera-Aponte; Christian J. Malpica-Nieves; Gerónimo Maldonado-Martínez; Héctor M. Maldonado; Serguei N. Skatchkov; Misty J. Eaton (Brain Sciences, 2021)
The authors wish to make the following corrections to this paper [...]